Corporate criminal liability of environmental corruption: The gap green crimes and state financial crimes - Rida Ista Sitepu; Nuchraha Alhuda Hasnda (Integritas: Jurnal Antikorupsi, 2025)
Indonesia’s enforcement of anti-corruption law in the environmental sector has made notable progress, as demonstrated by the cases involving the Governor of Southeast Sulawesi and ‘tin mining’ in Bangka Belitung. These cases highlight a systemic connection between corruption and ecological harm. Corruption in this context should be viewed not only as a financial crime against the state but also as an environmental offense. This study explores a convergent prosecutorial approach inspired by countries such as Ecuador, New Zealand, and India, which recognize nature as a legal subject under the “Rights of Nature”. The research addresses a gap in previous studies that focus on corruption prevention without considering ecological justice and protecting the environment as mandated by Article 28H and Article 33(4) of the 1945 Constitution and Law No. 32 of 2009. This study study argues for recognizing nature as a legitimate victim in environmental crimes and emphasizes that criminal verdicts should focus on ensuring substantive justice. This study, employing a normative-qualitative approach, proposes integrating anti-corruption and environmental regimes to create a more ecologically responsive criminal justice system in Indonesia.